Omitting follow-up food after initial hypoglycaemic treatment does not increase the likelihood of repeat hypoglycaemia - Vindedzis, S.; Marsh, B.; Sherriff, Jillian; Dhaliwal, Satvinder; Stanton, K. (Springer Healthcare Communications Ltd, 2013)
Introduction: Guidelines for self-treatment of hypoglycaemia specify initial treatment with quick-acting carbohydrate until blood glucose levels normalize and then follow-up with longer-acting carbohydrate. The few studies investigating follow-up show 29–57% omission or undertreatment with follow-up carbohydrate but do not investigate the association of this with repeat hypoglycaemia. This study aimed to develop, validate and administer a questionnaire to delineate this association. The timeframe targeted was 2 h post primary hypoglycaemic event (PPHE), the time influenced by long-acting carbohydrate. Methods: A questionnaire was generated, test–retest reliability assessed, and it was piloted on convenience samples from the target population. The final version was administered to all insulin-treated individuals attending an outpatient diabetes clinic over 4 weeks (169).Results: Questionnaire development: readability (69.6—standard/easy), test–retest reliability (Cohen’s kappa 0.57–0.91) and return rate (72.2%) were all acceptable. Questionnaire data: questionnaires were returned by 122 participants (63 males/59 females). Method of insulin administration was subcutaneous insulin injections (91%) and continuous subcutaneous insulin infusion (CSII) (9%). Repeat hypoglycaemia within 2 h PPHE was reported by 8.2% of respondents. There was no significant difference for age, gender and diabetes duration between those reporting repeat hypoglycaemia and those without. Consumption of follow-up longer-acting carbohydrate was reported by 58.2% of responders with 48% of these using long-acting and 52% medium-acting carbohydrate foods. Method of insulin administration and consumption of follow-up food were significantly associated with repeat hypoglycaemia (P = 0.015, 0.039) but presence or absence of symptoms and duration of action of carbohydrate were not significantly associated (P = 0.103, 0.629). Hierarchical logistic regression analysis showed omission of follow-up food PPHE was not a significant predictor of increased likelihood of repeat hypoglycaemia within 2 h PPHE, irrespective of method of insulin administration (P = 0.085). Conclusion: This study supports guidelines that recommend judicious, rather than routine use of follow-up longer-acting carbohydrate PPHE.